Animal Models of Phage Therapy - Penziner, Samuel; Schooley, Robert T.; Pride, David T. (Frontiers in Microbiology, 2021)
Amidst the rising tide of antibiotic resistance, phage therapy holds promise as an alternative to antibiotics. Most well-designed studies on phage therapy exist in animal models. In order to progress to human clinical trials, it is important to understand what these models have accomplished and determine how to improve upon them. Here we provide a review of the animal models of phage therapy in Western literature and outline what can be learned from them in order to bring phage therapy closer to becoming a feasible alternative to antibiotics in clinical practice.